PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L) PADA PEMBERIAN PUPUK BOKASHI ECENG GONDOK (Eichhornia crassipes) DAN PUPUK KCL - Nurseha, Nurseha; Sulastri, Melina; Sunarti, Sunarti (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
The main problem that arises on marginal land when it will be planted with green beans is the problem of soil fertility. This study aims to determine the response of growth and yield of green beans to the provision of water hyacinth bokashi and KCl fertilizer. The experiment with two factors was arranged with a completely randomized design. Bokashi fertilizer was tested in four dose levels, namely 1, 15, 30, and 45 tons ha-1. Each water hyacinth bokashi dose treatment was combined with four levels of KCl fertilizer, namely 0, 50, 100, and 150 kg ha-1. The results showed that there was an interaction between the water hyacinth bokashi dose treatment and the potassium fertilizer dose on the observation variables of plant height at 6 weeks after planting (cm), number of pods (pods), and number of full pods (pods). The best treatment was the 45 ton ha-1 dose treatment and a KCl fertillizer dose of 150 kg ha-1